Jaskra w oku bezsoczewkowym po operacji zaćmy wrodzonej bez wszczepu sztucznej soczewki wewnątrzgałkowej i z jej wszczepem - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate the incidence and individual risk factors for the development of aphakic glaucoma after congenital cataract surgery. Material and methods: We retrospectively reviewed the records of 113 eyes of children who underwent surgery for cataract between 1998 and 2002. Outcome variables studied included intraocular pressure, number of medication changes required over the course of the follow-up, and surgical interventions required. Results: We enrolled 113 eyes who had cataract extraction with IOL (101 eyes), or lensectomy with anterior vitrectomy (12 eyes). Median age during cataract surgery was 11.5 months. The median time to development of postoperative glaucoma was 3.2 years (range, 6 months – 10 years). Mean post cataract surgery follow-up was 6.2 years. Postoperative glaucoma developed in 9.7% of eyes of children with cataract. Postoperative open-angle glaucoma developed in 6 pseudophakic eyes and in 2 aphakic eyes; postoperative closed-angle glaucoma developed in 3 aphakic eyes. The mean follow-up period after the diagnosis of glaucoma was 3.8 years. During the course of follow-up, all of 11 eyes required 1-3 medication changes for controlling glaucoma and 3 of them (31.4%), required surgical intervention. Conclusions: Despite modern surgical techniques the incidence of aphakic glaucoma must be considered in all patients after pediatric cataract extraction. Our results show the importance of careful follow up of intraocular pressure after cataract surgery in children. Young patients undergoing cataract surgery should be monitored routinely for glaucoma.